ZEOLIT MEMPERTAHANKAN KUALITAS AIR DAN MENINGKATKAN PERTUMBUHAN LELE DUMBO (Clariasgariepinus) - Bambang Triyatmo (Universitas Gadjah Mada, 2003)
The objectives of this research were to know the effects of zeolite on the water quality and the growth of catfish. Catfishes were cultured in fiberglass containers (±24 l) with 5-10% of water exchange/container/day, for 3 months. The stocking density was 8 fishes/container (3 fishes/l water). Zeolite was added at 0, 125, 250, 500 mg/l/month.Result of this experiment indicated that zeolite at 125, 250, 500, mg/l/month decreased free CO2, alkalinity and NH3 of water during 3 months culture of catfish. The body weight increasment of catfish cultured in treated water with zeolit at 125, 250, 500 mg/l/month were 188, 195, and 222 g, respectively, which were higher than that of catfish cultured in untreated water.